Divergence of active site motifs among different classes of Populus glutaredoxins results in substrate switches - Xu, Hui; Li, Zhen; Jiang, Peng‐Fei; Zhao, Li; Qu, Chang; Van de Peer, Yves; Liu, Yan‐Jing; Zeng, Qing‐Yin (The Plant journal : for cell and molecular biology, 2022)
SUMMARY Enzymes are essential components of all biological systems. The key characteristics of proteins functioning as enzymes are their substrate specificities and catalytic efficiencies. In plants, most genes encoding enzymes are members of large gene families. Within such families, the contributions of active site motifs to the functional divergence of duplicate genes have not been well elucidated. In this study, we identified 41 glutaredoxin (GRX) genes in the Populus trichocarpa genome. GRXs are ubiquitous enzymes in plants that play important roles in developmental and stress tolerance processes. In poplar, GRX genes were divided into four classes based on clear differences in gene structure and expression pattern, subcellular localization, enzymatic activity, and substrate specificity of the encoded proteins. Using site‐directed mutagenesis, this study revealed that the divergence of the active site motif among different classes of GRX proteins resulted in substrate switches and thus provided new insights into the molecular evolution of these important plant enzymes. Significance Statement Elucidating the mechanisms of function differentiation of duplicate genes in large enzyme families is critical to understand the molecular evolution of important plant enzymes. By biochemical activity assays and site‐directed mutagenesis, this study revealed the contributions of active site motifs to the functional divergence of duplicate genes.